PENATALAKSANAAN FISIOTERAPI PADA KONDISI CARPAL TUNNEL SYNDROME (CTS) DEXTRA DENGAN MODALITAS ULTRASOUND (US) DAN TERAPI LATIHAN DI RSUD BENDAN KOTA PEKALONGAN - Nurul Faidah; Andung Maheswara (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Physiotherapy  management  in  condition  of  Carpal  Tunnel  Syndrome  (CTS)  dextra  with ultrasound (USD) and Exercise Therapy modalities. The manufacture of this paper was intended to provide  information,  knowledge  and  understanding  the  condition  of  Carpal  Tunnel  Syndrome (CTS) dextra that was characterized by the emphasis which the  median nerve as the cause of the problems such as pain, spasm, decreased muscle strength, range of joint motion, and the functional abilities. And the given modalities were ultrasound (USD) and  Exercise Therapy. Case  study  was  used  in  the  formulated  of  this  paper.  To  provide  an  effective  and  efficient handling,  carried  out  an  inspection  method  of  pain  with  Verbal  Descriptive  Scale  (VDS),  spasm examination  by  palpation,  examination  of  muscle  strength  with  Manual  Muscle  Testing  (MMT), range  of  joint  motion  checked  with  goneometer  and  the  functional  capabilities  usingWrist  hand disability index.  To  solve  those  problems,  ultrasound  (USD)  and  Exercise  Therapy  were  used  to  deal  with  the patient. After the therapies given for six times, obtained a decrease in pain of the patient, (pain at rest) T1 = 2, T6 = 1 (tenderness) T1 = 3, T6 = 1 (motion pain) T1 = 3, T6 = 1, decrease spasm T1 = 3, T6 = 1, an increase in muscle strength T1 = dorsal flexion 4, palmar flexion3+, ulnar deviation of 4+,  radial deviation 4+, into T6 = dorsal flexion 5, palmar flexion 4+,  ulnar deviation 5, radial deviation 5, an increase in range of motion of wrist T1 = S = 45-0-55, F = 30-0-20, T6 = S = 55-0- 55,  F  =  30-0-20,  the  increase  of  functional  ability  T1  =  34  (severe  dependence),  T6  =  13  (mild dependence).  From  the  results  obtained,  it  can  be  concluded  that  the  use  of  ultrasound  (USD)  and  Exercise Therapy  modalities  could  help  in  reduce  the  problems  that  arise  in  the  case  of  Carpal  Tunnel Syndrome (CTS) dextra.   Keywords:  Carpal  Tunnel  Syndrome  (CTS)  dextra,  Verbal  Descriptive  Scale  (VDS),  Spasm, Manual  Muscle  Testing  (MMT),  range  of  motion,  Wrist  and  Hand  Disability  Index, Ultrasound, Exercise Therapy.